PELATIHAN DAN PRAKTIK PEMBUATAN VLOG BISNIS BERBAHASA INGGRIS UNTUK MENDUKUNG PROMOSI PRODUK UMKM PASCA COVID-19 DI MALANG - Suharto, Ririn Pratiwi; Putra, Dhony Manggala (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
There are two MSME business owners in the Malang area, namely Mustika Jamur and Sari Kedelai Alfi who need a solution to increase their sales after the pandemic. The solution to help two MSME business owners is the idea of ​​training activities and the practice of making business vlogs in English. This activity held at Mustika Jamur and Sari Kedelai Alfi in Malang. Location selection is based on MSME products operating in the food and/or beverage sector in the Malang area. There are four stages of activities that have been carried out, including (1) providing knowledge about the meaning and concept of business vlogs, (2) providing knowledge about techniques for making business vlogs, (3) preparing a script for making business vlogs in English, and ( 4) practice making business vlogs in English. The results of this community service activity have had a good impact on the selected MSMEs. They are able to create vlogs which are used as promotional media material for MSMEs to increase sales. Vlogs made in English are also expected to attract consumers from abroad.